MONITORING OF CONSUMER ATTITUDES TO MEDICINES - N. B. Dremova; N. P. Yaroshenko; N. I. Afanaseva; S. V. Solomka (Фармакоэкономика)
Objective. Comparative analysis and monitoring of the population’s attitude to medicines through an assessment of their consumer qualities by visitors of pharmacies.Materials and Methods. Conducted two sociological survey thru the original questionnaires in 2002 and 2015 among pharmacy customers. Each survey included 380 respondents living in the cities of Central Russia. During the interviews, respondents were asked, among other things evaluate the 13 influencing their choice of consumer qualities of medicines. Six of these qualities characterize the pharmaceutical features and merchandising options are seven parameters of medicines. Statistical analysis used a set of indicators of variation statistics, ranking, rank correlation.Results. Ratings of consumer qualities of medicines are obtained for the studied years and changes in the whole period of monitoring. We have identified the priority characteristics of medicines which are essential for consumers, in particular: efficiency, clear information on the package, low cost, minor side effects, convenient way to receive.Conclusion. The revealed features of consumer attitudes to medicines should be taken into account pharmaceutical workers in information and consultative dealing with pharmacies visitors.